Effect of different dimension of CPW pentagonal island antenna with Sierpinski gasket fractal - Rashid, A. H. A.; Ahmad, B. H.; Aziz, M. Z. A.; Hassan, N. (2024)
This paper presents the effect of different dimensions on a dual band CPW Pentagonal Sierpinski gasket fractal patch antenna for WiMAX and WLAN applications. Four dissimilar parametric studies are chosen in this task to identify the effect of different antenna dimensions. At Antenna A, the first parametric study included a patch antenna with a different length size. The second parametric study of the different width dimensions for the pentagonal island at Antenna B follows. Antenna C is the focus of the third and fourth parametric studies. At this stage, various length and widths of mini pentagonal dimensions are considered its effect. This antenna has conducted at two different frequencies at 3.5 GHz and 5.8 GHz with return loss of - 31.70 dB and - 22.00 dB, respectively, and this results are acceptable for WiMAX and WLAN operation.